Production of Isa Brown Chicken Post-Vacination with Candidate of Egg Drop Syndrome (EDS) Vaccine Given Different Amount of Ration - N. M. A. L., Heppi; Dewi, G. A. M. K.; Wiyana, I K. A. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This study aims to determine the production of Isa Brown chicken eggs aged 18-22 weeks after vaccination with egg drop syndrome (EDS) vaccine candidates and given different amounts of commercial rations. The research was conducted at the Faculty of Animal Husbandry Teaching Farm Cage, University of Udayana Bukit Jimbaran for 4 weeks. The research material used by Isa Brown laying hens aged 18 weeks. The research design used Completely Randomized Design (CRD) consisting of 4 treatments, namely without vaccination with vaccine candidates and given 80 g (R0) commercial ration, without being vaccinated with vaccine candidates and given commercial ration 84 g (R1), after vaccination with candidates vaccine and given 80 g of commercial ration (R2), and after vaccination with vaccine candidates and given commercial rations 84 g (R3), each treatment used 5 replications each replication consisting of 3 chickens. The variables observed were hen day production, egg weight, egg shape index, feed consumption, feed convertion ration. The results showed that the daily treatment of R3 egg production increased and the treatment feed consumption R2 decreased (P<0,05) compared to treatments R0 and R1, but egg weight, egg shape index, and feed convertion ratio of treatments R0, R1, R2, R3 did not significantly different (P>0,05). Based on results of the study it can be concluded that Isa Brown's chicken after vaccination of EDS vaccine candidates was able to increase hen day production and reduce feed consumption but did not affect egg weight, egg shape index, and  feed convertion ration. Keywords : egg drop syndrome (EDS) vaccine candidate, Isa Brown, egg production, commercial rations